2014
DOI: 10.1111/pcn.12235
|View full text |Cite
|
Sign up to set email alerts
|

Sources of perceived social support associated with reduced psychological distress at 1 year after the Great East Japan Earthquake: Nationwide cross‐sectional survey in 2012

Abstract: Aim: Lack of social support has been associated with a higher level of psychological distress after disasters, but its relative associations with sources of support such as neighbors, friends, family, and others, are underreported. The present study assessed the associations of social support with psychological distress according to support source among the general population 1 year after the Great East Japan Earthquake.Methods: An online survey was completed by a Japanese national sample of 10 469 participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 33 publications
(58 reference statements)
2
11
1
2
Order By: Relevance
“…When compared to a study conducted in 2006, that reported that 3% of general Japanese population had serious mental distress [ 31 ], it appears that the prevalence of serious mental distress in this study is high. Further, a report on the prevalence of serious mental distress in the general population using a nationwide internet survey, conducted one year after the GEJE [ 12 ], also found the prevalence of serious mental distress was 8.9%, which was slightly lower than that in our study. Thus, the prevalence of serious mental distress in Miyagi Prefecture was higher than that of Japan before and after the GEJE.…”
Section: Discussioncontrasting
confidence: 87%
“…When compared to a study conducted in 2006, that reported that 3% of general Japanese population had serious mental distress [ 31 ], it appears that the prevalence of serious mental distress in this study is high. Further, a report on the prevalence of serious mental distress in the general population using a nationwide internet survey, conducted one year after the GEJE [ 12 ], also found the prevalence of serious mental distress was 8.9%, which was slightly lower than that in our study. Thus, the prevalence of serious mental distress in Miyagi Prefecture was higher than that of Japan before and after the GEJE.…”
Section: Discussioncontrasting
confidence: 87%
“…People who had the following characteristics or status were likely to have psychological distress: female, lost their family members, experienced residential damage, had anxiety about radioactive contamination, had difficult economic status, and had weak social support. [90][91][92][93][94][95][96][97][98][99][100][101][102][103][105][106][107][108][109][110][111][112][113][117][118][119][120]122,[124][125][126][127][128][129][132][133][134][135][136][137][138][139][140]143,144,147,151,152,155 Psychological effects of the...…”
Section: Mental Health Issuesmentioning
confidence: 99%
“…The results of this study indicated that the presence of pre-disaster acquaintances had a positive role in social support among mothers with infants and preschool-aged children in a post-disaster community. A previous study among the general population 1 year after the Great East Japan Earthquake and Tsunami indicated that support from neighbors contributed to a reduction of psychological distress as well as the provision of support from family members in the area affected by the disaster [ 28 ]. Our study results also showed that the presence of pre-disaster acquaintances was positively associated with child-rearing social support, especially mental/physical place of comfort and child-rearing support.…”
Section: Discussionmentioning
confidence: 99%